Thinking through sociality an anthropological interrogation of key concepts - Amit, Vered (New York Berhahn Books, 2015)
In this book, an international group of contributors train attention on the concepts of disjuncture, field, social space, sociability, organizations and network, mid-range concepts that are "good to think with." Neither too narrowly defined nor too sweeping, these concepts can be used to think through a myriad of ethnographic situations.
Includes bibliographical references and index.
Keywords: Ethnology; Social interaction; Anthropology